Pesan Moral yang Terdapat dalam Novel Paper Towns Karya John Green - Widya Aulia Pratiwi Rahmah (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2024)
Novel is a literary of work which contains a moral message. In every story there must be a good lesson that we can apply in everyday life. One of them is the novel Paper Towns by John Green which makes it interesting for researchers to examine "the moral message in the novel Paper Towns by John Green. The method used is descriptive method. Metode deskriptif kualitatif adalah metode yang bertujuan untuk menggambarkan, menjelaskan, dan menganalisis permasalahan yang didapat dalam sebuah penelitian (Aryanti, 2019). This study have a goal to analyze moral value in Paper Towns by John Green.